Tanggung Jawab Hukum Ortodontis Praktik Mandiri terhadap Pengelolaan Limbah Bahan Perawatan Ortodonti - Dewi, Luh De Puspita; Adriano, Adriano; Nurul, Nurul (Syntax Corporation, 2025)
The research aims to analyze the obligations of orthodontists in independent practice regarding waste management and their legal responsibilities for environmental pollution caused by the waste from orthodontic treatment materials.The study focuses on the legal responsibilities of orthodontists in managing waste to prevent pollution arising from the disposal of materials used in orthodontic treatments. This research employs a legal research method with a statutory approach and a conceptual approach. The results of the study indicate Independent practice orthodontists, in addition to working to provide health services and as managers of independent practices, have a legal obligation to manage the waste of orthodontic treatment materials produced in accordance with applicable regulations in Indonesia. the obligation to manage the waste produced includes the obligation to reduce, sort, temporarily store and cooperate with other parties for waste transportation and treatment. Independent practice orthodontists are legally responsible for environmental pollution arising from the impact of poor management of orthodontic treatment material waste, where legal responsibility includes administrative responsibility if independent practice orthodontists intersect with the problem of violation of permits and waste management procedures. Civil law liability, namely in the form of compensation and recovery of damage to the aggrieved party, and criminal law liability, namely if the orthodontist commits an unlawful act.